2008
DOI: 10.1213/ane.0b013e31817e616b
|View full text |Cite
|
Sign up to set email alerts
|

Factors Predictive of Poor Behavioral Compliance During Inhaled Induction in Children

Abstract: Factors predictive of poor behavioral compliance were age, previous anesthesia, preoperative tour attendance, preoperative preparation time and anxiety levels in the preoperative clinic. These factors, bundled into a predictive algorithm, may help identify children who could benefit from behavioral or pharmacological interventions and avoid use of interventions to those at low risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
51
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(62 citation statements)
references
References 22 publications
7
51
0
4
Order By: Relevance
“…Younger children (2-5 years of age) and patients who have been to the OR before are at higher risk of being stressed and uncooperative during the induction of anesthesia. 8 In addition, some patients will suffer from postoperative behavioral changes, including sleep difficulties, which may present to the pediatrician in the weeks after surgery. Recent studies have concluded that the likelihood of these maladaptive behaviors is higher if the child is anxious preoperatively.…”
Section: Introductionmentioning
confidence: 99%
“…Younger children (2-5 years of age) and patients who have been to the OR before are at higher risk of being stressed and uncooperative during the induction of anesthesia. 8 In addition, some patients will suffer from postoperative behavioral changes, including sleep difficulties, which may present to the pediatrician in the weeks after surgery. Recent studies have concluded that the likelihood of these maladaptive behaviors is higher if the child is anxious preoperatively.…”
Section: Introductionmentioning
confidence: 99%
“…All children received an inhalational induction with sevoflurane in an oxygen/nitrous oxide mixture in the presence of their parent or guardian. The induction compliance checklist consisting of 11 items was used to record the child's behaviour at induction [8]. Following induction of anaesthesia, an intravenous cannula was inserted and standard monitoring attached (ECG, pulse oximeter, non-invasive blood pressure, end-tidal gas analysis).…”
mentioning
confidence: 99%
“…The induction compliance measure, collected as part of the anesthesia quality assurance program, ensured that while changes were being made to the premedication order entry process, children who met criteria received premedication. 8 The numbers of cases conducted per week were monitored to ensure that while scheduling changes were being made, the volume of cases did not decrease.…”
Section: Methods Of Evaluation and Analysesmentioning
confidence: 99%
“…The second was to use a clinical algorithm to facilitate this early decision. 8 The third was to eliminate the routine prescription of acetaminophen for postoperative pain relief to be administered preoperatively in the SDS clinic. A literature search did not provide evidence to support the use of acetaminophen for this purpose.…”
Section: Figurementioning
confidence: 99%